Indentation and Transverse Diameter of the Meckel Cave: Imaging Markers to Diagnose Idiopathic Intracranial Hypertension - Kamali, A.; Sullivan, K.C.; Rahmani, F.; Gandhi, A.; Aein, A.; Arevalo, O.; Rabiei, P.; Choi, S.J.; Zhang, X.; Gabr, R.E.; Riascos, R.F. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Clinical and imaging manifestations of idiopathic intracranial hypertension should prompt early diagnosis and treatment to avoid complications. Multiple diagnostic imaging criteria are reported to suggest the diagnosis of idiopathic intracranial hypertension with questionable sensitivity and/or specificity. Increased intracranial pressure results in dilation of the perineural cisternal spaces such as the optic nerve sheaths and the Meckel cave. It may also cause protrusion of cisternal structures of the Meckel cave through the skull base foramina, which could result in indentation or a bilobed appearance of the Meckel cave. We investigated the changes in the Meckel cave in patients with proved idiopathic intracranial hypertension versus healthy controls.MATERIALS AND METHODS: We studied 75 patients with a diagnosis of idiopathic intracranial hypertension and 75 age-and sex-matched healthy controls. The transverse diameter of Meckel cave was measured in the axial and coronal planes of T2-weighted MR imaging sequences, and comparison was made between the 2 groups.RESULTS: The mean diameters of the Meckel cave on the coronal T2 plane in patients with idiopathic intracranial hypertension were 5.21  ± 1.22 mm on the right side and 5.16  ± 0.90 mm on the left side, while in the control group, they measured 3.89  ± 0.62 mm and 4.09  ± 0.68 mm, respectively (P value < .001). Of 75 patients with an approved diagnosis of idiopathic intracranial hypertension, 57 (76%) showed an indented Meckel cave as opposed to 21 (28%) in the control group.CONCLUSIONS: Our results confirm for the first time that the shape and size of the Meckel cave can be used as sensitive and specific diagnostic imaging markers for the diagnosis of idiopathic intracranial hypertension.APanterior-posteriorAUCarea under the receiver operating characteristic curveIIHidiopathic intracranial hypertensionMCMeckel cavePEpapilledemaTSStransverse sinus stenosis